Structure and Function of the Photosystem Supercomplexes - Gao, Jinlan; Wang, Hao; Yuan, Qipeng; Feng, Yue (Frontiers in Plant Science, 2018)
Photosynthesis converts solar energy into chemical energy to sustain all life on earth by providing oxygen and food, and controlling the atmospheric carbon dioxide. During this process, the water-splitting and oxygen-evolving reaction is catalyzed by photosystem II (PSII), while photosystem I (PSI) generates the reducing power for the reduction of NADP+ to NADPH. Together with their peripheral light-harvesting complexes (LHCs), photosystems function as multisubunit supercomplexes located in the thylakoid membranes of cyanobacteria, algae, and plants. Recent advances in single-particle cryo-electron microscopy (cryoEM), X-ray free electron laser (XFEL) and other techniques have revealed unprecedented structural and catalytic details concerning the two supercomplexes. Several high-resolution structures of the complexes from plants were solved, and serial time-resolved crystallography and “radiation-damage-free” femtosecond XFEL also provided important insights into the mechanism of water oxidation. Here, we review these exciting advances in the studies of the photosystem supercomplexes with an emphasis on PSII-LHCII, propose presently unresolved problems in this field, and suggest potential tendencies for future studies.